Pelleting is a successful method to eliminate the presence of Clostridium spp. from the digestate of biogas plants. (October 2015) - Pulvirenti, Andrea; Ronga, Domenico; Zaghi, Massimo; Tomasselli, Anna Rita; Mannella, Lorenzo; Pecchioni, Nicola
Abstract: Biogas production is increasing as a sustainable energy supply, with digestate resulting as a by-product of biogas plants. As a result, the high concentration of Clostridium spp. in digestate became a concern in dairy farming areas. Clostridium spores can contaminate soils and crops when digestate is used as fertilizer, causing a conflictual cohabitation of biogas with traditional cheese productions. In order to solve the problem, this study aimed to search for a technical solution enabling either a drastic reduction or the elimination of the content of Clostridium spp. within digestate. Results showed a complete elimination of Clostridium spp. in pelleted stored solid digestate; in addition, pelleting caused a reduction of pH and water mass fraction in terms of fresh weight, and a concentration of mineral nutrients compared to stored solid digestate. Pellet can represent a possible sustainable solution both in reducing potential risks linked to the presence of Clostridium spp. in digestate and in improving the transportation and distribution of high-value fertilizer. Hence, pelleting of solid digestate could offer a simple and efficient method to allow cohesistence of biogas plants and dairy farming. Highlights: Pelleting eliminate the presence of Clostridium spp. in solid digestate. Mineral nutrients are more concentrated in pellet solid digestate. Pelleted solid digestate is an alternative, sustainable and safe fertilizer.